The landscape of antibody binding in SARS-CoV-2 infection - Heffron, Anna S.; McIlwain, Sean J.; Amjadi, Maya F.; Baker, David A.; Khullar, Saniya; Armbrust, Tammy; Halfmann, Peter J.; Kawaoka, Yoshihiro; Sethi, Ajay K.; Palmenberg, Ann C.; Shelef, Miriam A.; O’Connor, David H.; et al. (PLOS Biology, 2021)
Profiling of antibody binding from naïve and COVID-19 convalescent human sera to the entire proteome of SARS-CoV-2 and other human, bat and pangolin coronaviruses identifies 79 B cell epitopes throughout the SARS-CoV-2 proteome, finding that the most sensitive and specific binding occurred in the membrane (M) protein, and revealing cross-reactivity patterns.